THE ROLE OF THE COMMUNITY IN THE DEVELOPMENT OF MANGROVE FOREST ECOTOURISM IN PASAR BANGGI, REMBANG REGENCY - Sholeh, Sofyan; Evianovita, Dwi Intan Nur; Mayasari, Annita Yuli; Sudewo, Anung Ari (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2024)
Mangrove forests are one of the most productive ecosystems, located in tropical and subtropical coastal waters and river estuaries. Mangroves provide benefits to humans and the environment by providing shelter for brackish water organisms such as fish and shrimp. Pasar Banggi Mangrove Forest in Rembang Regency has a geographic location with a geographical position of 6º41'52.45